Potential Roles of Muscle-Derived Extracellular Vesicles in Remodeling Cellular Microenvironment: Proposed Implications of the Exercise-Induced Myokine, Irisin - Darkwah, Samuel; Park, Eun Jeong; Myint, Phyoe Kyawe; Ito, Atsushi; Appiah, Michael G.; Obeng, Gideon; Kawamoto, Eiji; Shimaoka, Motomu (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EVs) have emerged as key players of intercellular communication and mediate crosstalk between tissues. Metastatic tumors release tumorigenic EVs, capable of pre-conditioning distal sites for organotropic metastasis. Growing evidence identifies muscle cell-derived EVs and myokines as potent mediators of cellular differentiation, proliferation, and metabolism. Muscle-derived EVs cargo myokines and other biological modulators like microRNAs, cytokines, chemokines, and prostaglandins hence, are likely to modulate the remodeling of niches in vital sites such as liver and adipose tissues. Despite the scarcity of evidence to support a direct relationship between muscle-EVs and cancer metastasis, their indirect attribution to the regulation of niche remodeling and the establishment of pre-metastatic homing niches can be put forward. This hypothesis is supported by the role of muscle-derived EVs in findings gathered from other pathologies like inflammation and metabolic disorders. In this review, we present and discuss studies that evidently support the potential roles of muscle-derived EVs in the events of niche pre-conditioning and remodeling of metastatic tumor microenvironment. We highlight the potential contributions of the integrin-mediated interactions with an emerging myokine, irisin, to the regulation of EV-driven microenvironment remodeling in tumor metastasis. Further research into muscle-derived EVs and myokines in cancer progression is imperative and may hold promising contributions to advance our knowledge in the pathophysiology, progression and therapeutic management of metastatic cancers.